2016
DOI: 10.1111/ajt.13769
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Discard Rate After the Introduction of the Kidney Donor Profile Index (KDPI)

Abstract: Since 3/26/2012, the Kidney Donor Profile Index (KDPI) has been provided with all deceased-donor kidney offers, with the goal of improving the ECD indicator. Although an improved risk index may facilitate identification and transplantation of marginal yet viable kidneys, a granular percentile system may reduce provider-patient communication flexibility, paradoxically leading to more discards (“labeling effect”). We studied the discard rates of the kidneys recovered for transplantation between 3/26/2010-3/25/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(185 citation statements)
references
References 17 publications
5
179
1
Order By: Relevance
“…At least in the USA, KDPI has a potential to influence the clinical decision on whether to accept or discard a donor kidney, but there is no uniform view on its robustness since the graft outcomes depend also on other donor factors and recipient characteristics. Up to now, there have been a lot of debates about KDPI, and while some authors found its use increased the acceptance of donors and lead to rise in transplantation rate [7] and robustly predicted kidney graft survival [8], others doubted about its generalizability to non-US [9] and non-adult populations [10, 11], and caution about formal KDPI use as a criterion of organ discard [12, 13]. KDPI > 85% is thought to be equivalent to an extended criteria donor (ECD) kidney (while the KDPI is based on 10 parameters, the historical ECD definition is based on only 4 parameters), but almost twice less donors were classified as ECD according to KDPI> 85% in comparison with the historical ECD definition, and thus were accepted for transplantation [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in the USA, KDPI has a potential to influence the clinical decision on whether to accept or discard a donor kidney, but there is no uniform view on its robustness since the graft outcomes depend also on other donor factors and recipient characteristics. Up to now, there have been a lot of debates about KDPI, and while some authors found its use increased the acceptance of donors and lead to rise in transplantation rate [7] and robustly predicted kidney graft survival [8], others doubted about its generalizability to non-US [9] and non-adult populations [10, 11], and caution about formal KDPI use as a criterion of organ discard [12, 13]. KDPI > 85% is thought to be equivalent to an extended criteria donor (ECD) kidney (while the KDPI is based on 10 parameters, the historical ECD definition is based on only 4 parameters), but almost twice less donors were classified as ECD according to KDPI> 85% in comparison with the historical ECD definition, and thus were accepted for transplantation [12].…”
Section: Discussionmentioning
confidence: 99%
“…KDPI > 85% is thought to be equivalent to an extended criteria donor (ECD) kidney (while the KDPI is based on 10 parameters, the historical ECD definition is based on only 4 parameters), but almost twice less donors were classified as ECD according to KDPI> 85% in comparison with the historical ECD definition, and thus were accepted for transplantation [12]. However, the usage of kidneys with higher KDPI, and particularly > 85%, has declined in the USA [12, 13], that leaves some potential recipients on dialysis. Of note, even the recipients of kidneys with KDPI > 85% were at a much lower risk of death 2 years after transplant compared to those remaining on dialysis waiting for low-KDPI kidneys [13].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, an additional objective test could help in decisions on acceptance and allocation of donor kidneys, thereby increasing donor potential. Discarding kidneys for transplantation cannot be justified on the basis of such a test, although acceptance may be increased for ECD kidneys with a kidney donor profile index ,85 and standard criteria donor kidneys with a kidney donor profile index .85, for which discard rates could be reduced (4).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in ECD kidneys, predictive information on organ function could drastically increase transplant availability (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although the hope was to reduce the discard rate of "marginal" or "extended criteria donor (ECD)" kidneys allocating them in a better way, the discard rate did not differ compared to the ECD era. 1 The transplantation community continues to seek ways to improve kidney allocation in order to provide acceptable (or even better) outcomes using the most possible deceased donor kidneys reducing the discard rate. One way to boost the use of higher-risk kidneys is allocating them as dual kidney transplantation (DKT).…”
Section: Is the Kidney Donor Profile Index (Kdpi) Universal Or Unosspmentioning
confidence: 99%